2015
DOI: 10.1186/s12911-015-0149-3
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the efficiency of trial-patient matching: automated clinical trial eligibility Pre-screening for pediatric oncology patients

Abstract: BackgroundManual eligibility screening (ES) for a clinical trial typically requires a labor-intensive review of patient records that utilizes many resources. Leveraging state-of-the-art natural language processing (NLP) and information extraction (IE) technologies, we sought to improve the efficiency of physician decision-making in clinical trial enrollment. In order to markedly reduce the pool of potential candidates for staff screening, we developed an automated ES algorithm to identify patients who meet cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 21 publications
(22 reference statements)
2
73
0
Order By: Relevance
“…The key goals of this process are to (1) identify those populations who meet the inclusion criteria for a study, and (2) facilitate the most efficient workflow for enrollment of those patients into the correct trial [82]. Ni et al showed that a text-mining-based screening system could accomplish both goals [83]. They identified patient phenotypes using text mining of notes and billing code data to enable automated patient screening.…”
Section: 5 Clinical Trial Recruitmentmentioning
confidence: 99%
“…The key goals of this process are to (1) identify those populations who meet the inclusion criteria for a study, and (2) facilitate the most efficient workflow for enrollment of those patients into the correct trial [82]. Ni et al showed that a text-mining-based screening system could accomplish both goals [83]. They identified patient phenotypes using text mining of notes and billing code data to enable automated patient screening.…”
Section: 5 Clinical Trial Recruitmentmentioning
confidence: 99%
“…Pakhomov and colleagues used it to identify patients suffering from angina pectoris [131] or heart failure [132]. Ni and colleagues used it to improve oncology trial eligibility screening [130], and Weng and Boland to represent and extract trial eligibility criteria [133,134]. Extracting information to improve treatment and follow-up of patients has been applied to pancreatic [135] and colon neoplasms detection [136], thromboembolism and incidental findings [137], adverse events and errors detection [137], and patients acuity prediction [138].…”
Section: F Extraction Of Information From Unstructured Clinical Datamentioning
confidence: 99%
“…Various data and attribute values were extracted to support peripheral artery disease and heart failure research in the eMERGE network [128], and to support obesity research [129]. Study subjects recruitment is a constant struggle, and adding more detailed information extracted from unstructured data to existing diagnostic codes significantly improves it [130]. Pakhomov and colleagues used it to identify patients suffering from angina pectoris [131] or heart failure [132].…”
Section: F Extraction Of Information From Unstructured Clinical Datamentioning
confidence: 99%
“…Papers reviewed included the use of natural language processing on clinical notes, case-based reasoning, and automated analysis of audiograms [42][43][44][45]. The Internet is having an increased impact on patient recruitment.…”
Section: Enrolling Participants Into Studiesmentioning
confidence: 99%